2020
DOI: 10.1007/s42452-020-2265-7
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible superparamagnetic nanoparticles with ibuprofen as potential drug carriers

Abstract: This article describes the synthesis, characterization, in vitro cytotoxic and genotoxicity evaluation of chitosan-iron oxide nanoparticles (Fe 3 O 4 -CS) as vehicles for ibuprofen (IBU) molecule. Magnetite (Fe 3 O 4 ) nanoparticles were synthesized by co-precipitation of iron salts and coated with chitosan, leading to the formation of Fe 3 O 4 -CS hybrid nanoparticles, and then IBU was adsorbed on the surface of the modified nanoparticles. The physicochemical, morphological, and magnetic properties of the nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…In addition, the bands at 2630, 2725 and 2930 cm À1 correspond to C-H groups with different orientations in the IBU molecule. [48][49][50] The PEG/IBU electrode showed the same vibrational peaks for IBU; compare the purple and pink curve in Fig. 4c.…”
Section: Infrared Spectroscopy Analysis For the Sc Electrodesmentioning
confidence: 83%
“…In addition, the bands at 2630, 2725 and 2930 cm À1 correspond to C-H groups with different orientations in the IBU molecule. [48][49][50] The PEG/IBU electrode showed the same vibrational peaks for IBU; compare the purple and pink curve in Fig. 4c.…”
Section: Infrared Spectroscopy Analysis For the Sc Electrodesmentioning
confidence: 83%
“…The decrease in adsorption capacity at high temperature implied the reduction of physical interaction between ibuprofen and the iron oxide active site. High temperature also increased the diffusion rate of ibuprofen from the surface of adsorbent and improved repulsion between the adsorbed ibuprofen molecules creating a steric barrier [48][49][50]. In general, the results showed that temperature is an important parameter to control the efficiency of ibuprofen removal.…”
Section: Ibuprofen Removal Via Adsorptionmentioning
confidence: 86%
“…Furthermore, the surface area of iron oxide is relatively smaller than that of most adsorbent, thus unable to adsorb a high concentration ibuprofen resulting in the decrease of adsorption capacity [47]. The decrease of adsorption sites saturated with ibuprofen molecules is predicted to have a strong influence in decreasing the adsorption capacity by two times, as observed in 50 mg/L and 100 mg/L of ibuprofen concentrations [48]. The percentage of removal when using a high concentration solution at 100 mg/L was observed in only 18.7%, in agreement with previously reported studies that suggested the available active sites were already saturated by ibuprofen moieties [49].…”
Section: Ibuprofen Removal Via Adsorptionmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) have received wide attention in the last two decades, because of their distinctive physical, electrical, mechanical and liquid crystal properties [1]. However, SWCNTs with their extraordinary chemical and thermal stability [2] prove to be highly promising materials by providing a better nanoplatform for enhanced biomedical applications including those of drug delivery [3], medical imaging, nanosensors and cancer targeting [4,5]. Furthermore, the incorporation of functional groups on SWCNTs surface by covalent approach creates a facile nanomaterial with increased biological properties and its application has been explored extensively [6].…”
Section: Introductionmentioning
confidence: 99%
“…Fig.3a Raman image at different scan region: pink(1), blue(2), red (3) and green (4) and Raman spectra of b PSPA pink(1), blue(2), red (3) and green(4) …”
mentioning
confidence: 99%